KONJUNGSI KOORDINATIF DALAM BERITA POLITIK HARIAN PAGI RIAU POS - Bella Nissa; M. Nur Mustafa; Mangatur Sinaga (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research discusses about coordinating conjunction in political news Daily morning Riau Pos. This study aims to determine the type of coordinating conjunction and to describe the use of relationships of coordinated conjunction meaning in the political news of Riau Pos Daily Morning Post. Research is useful theoretically and practically. This research is a type of qualitative research and using descriptive method. The technique used in data collection in this research is documentation technique. The data that have been collected and then analyzed with several stages, namely reading activity repeatedly and carefully in the data, identify the data and describe the data, and concluded the research results. This research data comes from the discourse of political news in the newspaper Daily Morning Riau Pos. From the research that has been done, the researcher finds 240 data, that is 163 data conjunction and, 3 data conjunction let alone, 5 data conjunction and, 12 data conjunction other than, 3 data conjunction with, 3 data conjunction before, 3 data conjunction then 1 data conjunction data, but 1 conjunction data but 1 conjunction data but 1 conjunction data but 1 conjunction data instead of 3 conjunction data whereas, even 3 conjunction data, 10 data conjunctions only, 4 data conjunction is, 9 data conjunction so, 1 data conjunction therefore, and 1 data conjunction thus. So, the most data is the conjunction data and. Based on the result of the research, it can be concluded that there are (1) the coordination conjunction relation of the meanings of addition: and, moreover, and, besides, and with; (2) coordinated conjunctive relation meaning meaning: then and then; (3) the coordinating conjunction of the meaning of the election; or; (4) a coordinated conjunction of the meaning of resistance: but, however, but rather, even, and whereas; (5) the coordination conjunction relation of more meaning: even; (6) a coordinating conjunction of correlation means of meaning: only; (7) the coordinating conjunctive relation of the meaning of restriction: only; (8) the coordinating conjunction relation meaning meaning: is; and (9) the coordinating conjunction of the meaning of the inference: so, therefore, and thus. The use of a coordinated conjunction in Riau Pos Daily Morning connects words with words, words with phrases, phrases with phrases, phrases with clauses, words with clauses, phrases with clauses, and clauses with clauses.Key Words : conjunctions, coordinative conjunctions, meaning relationships